Rags to riches; Real love; From guns to God; Just got lucky [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Summary: Portrays the real life stories of Cyrus Aparri, Mari Kaimo and Enchang Agudo, Binbong Crisologo, Manila Mayor Alfredo Lim and other.